Digital literacy in EFL learning: University students’ perspectives - Pertiwi, Intan; Rojab Siti, Rodliyah (JEES (Journal of English Educators Society), 2022)
The 21st century has widely opened the opportunity for society, specifically in the educational party, to excel their performance in digital literacy. This relates to the competence required in accessing information using media and ICT tools in the process of learning. Technology integration in EFL learning has been a common issue, yet studies in digital literacy in language learning are still scarcely being conducted. This study explores university students’ digital literacy skills and their perspectives on digital literacy in EFL learning. Two instruments were utilized through a qualitative method, including a questionnaire and interview. The findings showed some aspects of digital literacy influencing students’ EFL learning. This involves students’ information literacy, ICT and media literacy, and their perspectives on digital literacy. The result indicated that EFL university students are encouraged to apply digital literacy since almost all learning components are integrated with digital technologies. As a consequence, they showed high awareness to keep up with the latest issue on digital literacy in their EFL learning. HIGHLIGHTS: Digital literacy relates to the competence required in accessing information using media and ICT tools in the learning process EFL university students are required to apply digital literacy skills to their learning process for the learning activity is mostly integrated with information and digital technologies. Providing with the data obtained from questionnaire and interview, EFL university students revealed the urgency of being literate in digital with both challenges and advantages to contribute to one of the essential skills for 21 st century’s future profession.